2021
DOI: 10.1039/d0ob02398a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbonyl on the isomerization of a galanthan ring system and total synthesis of (±)-β-lycorane

Abstract: Lycorine-type alkaloids are privileged structures in the drug development due to its attractive biological activities. In this paper, the carbonyl on the C ring was proved to have played a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Besides cycloaddition approaches, other groups have taken advantage of conjugated additions to prepare both racemic and asymmetric lycoranes. [60,61] For instance, the synthesis of (�)-γ-lycorane was reported by Tu (Scheme 13). [62] He took advantage of the kinetic enolate of 93, which was subjected to a Michael reaction with nitro alkene 94 to form compound 95.…”
Section: Conjugate Addition Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides cycloaddition approaches, other groups have taken advantage of conjugated additions to prepare both racemic and asymmetric lycoranes. [60,61] For instance, the synthesis of (�)-γ-lycorane was reported by Tu (Scheme 13). [62] He took advantage of the kinetic enolate of 93, which was subjected to a Michael reaction with nitro alkene 94 to form compound 95.…”
Section: Conjugate Addition Approachesmentioning
confidence: 99%
“…This oxoindole has been reported by the same group as an intermediary for the synthesis of γlycorane. [157] Liu et al [182] also reported a synthesis of β-lycorane through Michael addition-elimination reactions. Reaction between 421 and nitroolefin 174 in basic conditions produced 422 in 91 % yield.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Recently, we have developed an intermolecular Michael addition of racemic nitroalkene with aryl lithium reagent as a key strategy to accomplish the total synthesis of (±)-βlycorane (Figure 2B). 18 This Michael addition was easy to handle, cost-effective, and highly diastereoselective. We envisioned that the use of a chiral nitroalkene in the similar Michael addition may afford the key chiral intermediate leading to (+)-pancratistatin (1), and consequently allowed its efficient preparation (Figure 2C).…”
mentioning
confidence: 99%
“…Recently, we have developed an intermolecular Michael addition of racemic nitroalkene with aryl lithium reagent as a key strategy to accomplish the total synthesis of (±)-β-lycorane (Figure B) . This Michael addition was easy to handle, cost-effective, and highly diastereoselective.…”
mentioning
confidence: 99%
“…Activities such as AChE inhibitory, anticancer, cytostatic, antivirus, and antifungal activities have been discovered in these natural products. , Among >600 Amaryllidaceae alkaloids, lycorane is a representative of the lycorine class in which three contiguous chiral centers are embedded in a minimally substituted framework . Despite the extensive effort by various research groups to implement an effective total synthesis of lycorane since the first report by Hill and co-workers in 1962, the published synthetic strategies remain mostly racemic, and the asymmetric syntheses, particularly catalytic asymmetric ones, are limited . Furthermore, in known asymmetric methods, a thorny issue, asymmetric total synthesis for all stereoisomers, could not be tackled.…”
mentioning
confidence: 99%